Kecemasan Belajar Statistik Pendidikan bagi Mahasiswa: (Studi Kasus pada Mahasiswa Fakultas Tarbiyah Institut Agama Islam Miftahul Ulum Pamekasan) - Abdurrahman Rifki (EDUTHINK: Jurnal Pemikiran Pendidikan Islam, 2022)
Learning Anxiety experienced by tarbiyah faculty students requires proper prevention, so that the achievement of lecture goals can be achieved optimally. Not only that, the acute anxiety experienced can have a negative impact on the psychological level of the students themselves. The research method used is a descriptive approach with a case study, namely a study of data collection techniques as follows: in-depth interviews, observation and documentation. While the data analysis technique used in the study is a qualitative analysis technique. The results of this study indicate that the forms of Anxiety Learning Education Statistics for Students of the Tarbiyah Faculty of the Islamic Institute of Religion Miftahul Ulum Pamekasan include dimensions of physical symptoms, dimensions of cognitive symptoms and dimensions of behavioral symptoms. Meanwhile, the factors causing the Anxiety of Studying Education Statistics for Students of the Tarbiyah Faculty of the Islamic Institute of Religion Miftahul Ulum Pamekasan include internal and external factors.